Controls on the Emplacement of Kimberlites and Alkalic Rock-carbonatite Complexes in the Canadian Shield and Surrounding Regions (a098ab63-0a80-4049-a6b9-fbdb149046b1) - K. D. Card; B. V. Sanford; G. M. Card (Canadian Institute of Mining, Metallurgy and Petroleum, 1997)
The Canadian Shield and its extensions are traversed by an orthogonal system of north-west and northeast trending arch-style uplifts. These basement arches were formed by repeated vertical movements along pre-existing structures during compressional and extensional tectonism connected with events in surrounding Proterozoic and Phanerozoic orogens and ocean basins. The arches in?uenced patterns of sedimentation and tectonism in the intervening epicratonic basins andmarginal platforms throughout the Proterozoic and Phanerozoic. Movements on the arch structuresalso triggered minor magmatism and controlled the location and timing of alkalic rock-carbonatite, kimberlite, and related intrusions in the Canadian Shield, the Western Canada Sedimentary Basin, and West Greenland.